Prenatal diagnosis of exomphalos and prediction of outcome - K. Nitzsche (Nature Portfolio, 2021)
Abstract The aim of this study was to detect a parameter for predicting prenatal complications or postnatal surgical options after detecting a fetal exomphalos. This was a retrospective analysis of prenatal diagnosis and outcome of fetuses with 41 cases of exomphalos in between 2007 and 2017, considering the measurement of ratios. The 41 fetuses with exomphalos were examined, 34 cases (82.9%) with karyotyping and 16 cases (39%) with an abnormal karyotype. Outcome of 39 cases showed 6 abortions (15.4%), 15 terminations (38.5%), an intrauterine fetal death (2.5%) and 17 alive babies (43.6%), which were grouped in two: small exomphalos (n = 6, 35.3%) and big exomphalos (n = 11, 64.7%). Maximal diameter of exomphalos/abdomen circumference-ratio (EDmax/AC-ratio) with a cut-off of 0.24 showed a better predictive value of postnatal primary closure. Exomphalos is correlated with abnormal karyotype. EDmax/AC-ratio gives the best prediction for postnatal primary closure of the defect.